ETOS KERJA KEPALA SEKOLAH SDN 1 TRI MAKMUR JAYA MENGGAALA - Sutiyono (UNISAN JURNAL, 2024)
This study was directed to examine top to bottom the commitment of interdisciplinary Islamic examinations in fortifying strict control based Islamic schooling. Building Islamic schooling in light of strict balance through interdisciplinary Islamic examinations is one of the connections that can’t be isolated. The methodology used in this paper is graphic subjective where the initial step is to track down data and depict it, then gather information deliberately, then make a sense of it clearly. This exploration is a sort of library research since it centers around information gathered from library sources. The consequences of the examination show that strict control and logical mix in interdisciplinary Islamic examinations are a solitary connection in the chain. Balance in the advanced period like today still actually should be carried out, given the fortunes of Indonesia’s variety and variety which should be kept up even amidst innovation. Endeavors to construct strict control can start with illuminating the mentality to continuously be fair, not unreasonable, adjusted, and live as one with all components of society. Strict balance in Islamic training is done by fortifying the logical establishment that is coordinated with Islamic lessons. The act of strict control can be started from the most minimal components such as family schooling, as well as at the tertiary level.